Internalisasi Nilai-nilai Multikultural dalam Tafsîr Al-RÄzi pada Pengembangan Pendekatan Pembelajaran Tafsir - Hidayat, M.Noor (Jurnal Studi Agama dan Masyarakat, 2015)
Â This article contains about study of multicultural values in the tafsÃ®r ImÄm FakhruddÃ®n Al-RÄzÃ® (MafÄtÃ®á¸¥ul Ghaib), which has different specification from other tafsir in the same era. It includes many arguments about theology and fiqh. Furthermore, the multicultural values in this tafsÃ®r are implemented on the development approach of learning tafsÃ®r. This study used library research with phenomenology approach by seeing the reality of tafsÃ®r ImÄm FakhruddÃ®n Ar-RÄzÃ® which is accepted and refered by many of firqah, besides tafsÃ®r MaudhÅ«âi is used tool to make the study of tafsir ImÄm FakhruddÃ®n Ar-RÄzÃ® deeper. The result of this study consist of two parts: 1) An explanation of multicultural values concepts in tafsÃ®r MafÄtÃ®á¸¥ul Ghaib, 2) Multicultural approach learning as the result of implementing multicultural values on learning approach.